2023
DOI: 10.1093/femsle/fnad051
|View full text |Cite
|
Sign up to set email alerts
|

Function of a hydrophobin in growth and development, nitrogen regulation, and abiotic stress resistance of Ganoderma lucidum

Abstract: Fungal hydrophobins have many important physiological functions, such as maintaining hydrophobicity and affecting virulence, growth, and development. In Ganoderma lucidum, the molecular regulation mechanisms of hydrophobins in mushroom are unclear. In this study, we investigated a hydrophobin protein 1 (Hyd1) in G. lucidum, which belongs to the fungal Class I hydrophobins. The hyd1 gene was highly expressed during the formation of primordia, and expression was the lowest in fruiting bodies. Through the constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In Flammulina filiformi s, gene silencing of the hydrophobin hyd9 has obvious effects on primordia development (Tao et al 2019 ). Furthermore, in G. lucidum , it was reported that the hydrophobin Hyd1 is important for nitrogen regulation and resistance to heat, cell wall, and salt stresses (Qiao et al 2023 ). Based on these studies, hydrophobins are assumed to play important roles in the development of vegetative hyphae and fruiting bodies in many basidiomycetes.…”
Section: Hydrophobinsmentioning
confidence: 99%
“…In Flammulina filiformi s, gene silencing of the hydrophobin hyd9 has obvious effects on primordia development (Tao et al 2019 ). Furthermore, in G. lucidum , it was reported that the hydrophobin Hyd1 is important for nitrogen regulation and resistance to heat, cell wall, and salt stresses (Qiao et al 2023 ). Based on these studies, hydrophobins are assumed to play important roles in the development of vegetative hyphae and fruiting bodies in many basidiomycetes.…”
Section: Hydrophobinsmentioning
confidence: 99%